2005
DOI: 10.1007/s10735-004-6165-8
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical detection of estrogen receptor alpha in the growing and regressing ovaries of newly hatched chicks

Abstract: The aim of this study was to detect the presence of estrogen receptor alpha in different cell subpopulations of the growing left and regressing right ovaries from newly hatched chicks, by immunohistochemical methods, using an indirect immunoperoxidase technique. Newly hatched chicks were killed by decapitation and the growing left and regressing right ovaries were removed and processed for histological and immunohistochemical studies. The percentage of estrogen receptor alpha (ERalpha) immunostained cells and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 35 publications
0
3
0
1
Order By: Relevance
“…The significance of asymmetric expression of ER and other embryonic stem cell markers in chicken embryos is still unknown. However, the germinal epithelial cells were reported to be estrogen target cells acting via estrogen receptor (Morán, 2005). From our pervious study, we found that in ovo exposure of phytoestrogen to male quail embryo caused thickening of the cortex of the left male gonad .…”
Section: Discussionmentioning
confidence: 82%
“…The significance of asymmetric expression of ER and other embryonic stem cell markers in chicken embryos is still unknown. However, the germinal epithelial cells were reported to be estrogen target cells acting via estrogen receptor (Morán, 2005). From our pervious study, we found that in ovo exposure of phytoestrogen to male quail embryo caused thickening of the cortex of the left male gonad .…”
Section: Discussionmentioning
confidence: 82%
“…5 A). ERα is the nuclear receptor that is essential for normal ovarian differentiation ( 34 ). LIM homeobox protein 9 (LHX9) is a transcription factor critical for gonad development ( 35 ).…”
Section: Resultsmentioning
confidence: 99%
“…This implied that in chicken SOX9 could not activate AMH as in mammals, consistent with the expression profiles of SOX9 and AMH reported by different researchers [Kent et al, 1996;Oreal et al, 1998;Shimada, 2002], as they found SOX9 expression appears in male gonads 1 day after the onset of AMH expression. Estrogen regulates gene expression, female sexual differentiation and female secondary sexual characteristics by binding to and activating the nuclear estrogen receptors [Morán, 2005], i.e. ER ␣ and ER ␤ , which belong to the nuclear receptor superfamily of ligand-dependent transcription factors [Mangelsdorf et al, 1995;Di Croce et al, 1999].…”
Section: Control Gonadmentioning
confidence: 99%